ChemInform Abstract: Synthesis, Structure, and Superconductivity in the New‐Structure‐Type Compound: SrPt6P2. Issue 16 (April 2015) - Lv, Bing; et al., et al.
Abstract SrPt6P2 is prepared by solid state reaction of stoichiometric amounts of Sr, Pt, and pre‐reacted PtP2 (Al2O3 crucible in evacuated silica tube, 1.